(untitled) (The Pretoria Student Law Review, 2021)
The history of South African law is quite unique. It has aspirations of transformative constitutionalism, yet the law is deeply rooted in the common law. Of particular interest are the roles of two principles in the South African law namely; pacta sunt servanda, which is one of the principles found in the common law of contract; and ubuntu, which is a unique African principle of humanness. The law of contract and the Constitution exist side-by-side, however, this is not without conflict. The article will provide a gentle walk through the principles in the law of contract, the Mohamed’s v Southern Sun case, and will finally comment on the applicability of the principle of ubuntu versus that of the principle of pacta sunt servanda.